Development of a decision-making system based on the mandala of water and agricultural sustainability - Everaldo Júnior Borges Garcia de Pádua; Fabrício Barros Gonçalves; Layanne Andrade Mendonça (The Journal of Engineering and Exact Sciences)
This article aimed to develop an innovative decision support tool for sustainable water and agricultural management in river basins, using the Mandala of Water and Agricultural Sustainability. The system was built with technologies such as Django and Plotly, allowing a facilitating interface for water resources management with inclusive and participatory decision-making. A free web application was created, paving the way for user testing, updates based on results and final launch of the tool. It is believed that this will promote greater accessibility to information and involvement of social actors in water and agricultural management, resulting in more integrated and sustainable decisions.